2018
DOI: 10.1016/j.earscirev.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Coupling soil water processes and the nitrogen cycle across spatial scales: Potentials, bottlenecks and solutions

Abstract: Interactions among soil water processes and the nitrogen (N) cycle govern biological productivity and environmental outcomes in the earth's critical zone. Soil water influences the N cycle in two distinct but interactive modes. First, the spatio-temporal variation of soil water content (SWC) controls redox coupling among oxidized and reduced compounds, and thus N mineralization, nitrification, and denitrification. Secondly, subsurface flow controls the movement of water and dissolved N. These two processes int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 113 publications
0
48
0
Order By: Relevance
“…Similarly, Di, Cameron, Podolyan, and Robinson () observed that larger soil moisture contents led to a considerable increase in N 2 O (nitrous oxide) emissions in grassland soil, which the authors attributed to the growth of ammonia oxidizing and denitrifying communities. Zhu et al () also showed that increased soil water content can lead to large N 2 O emissions through denitrification. Moreover, soil pH was negatively correlated with nutrient concentrations in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Di, Cameron, Podolyan, and Robinson () observed that larger soil moisture contents led to a considerable increase in N 2 O (nitrous oxide) emissions in grassland soil, which the authors attributed to the growth of ammonia oxidizing and denitrifying communities. Zhu et al () also showed that increased soil water content can lead to large N 2 O emissions through denitrification. Moreover, soil pH was negatively correlated with nutrient concentrations in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Soil is characterized by spatial heterogeneity, structural complexity and biological diversity (Tian, Chen, Zhang, Melillo, & Hall, ; Zhang, Lu, Song, Guo, & Xue, ). Horizontal and vertical nutrient characteristics are both influenced by a variety of environmental factors such as hydrology, topography, climate and soil parent materials (Zhu, Castellano, & Yang, ). In wetland ecosystems, hydrological regimes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The SON content was significantly correlated with the SOC content due to primary source SOM [46]; thus, the SON distribution was also affected by straw non-recycling and tillage practices. Extraneous inorganic N, synthetic N fertilizer, and atmospheric N deposition can also be transformed into SON through uptake and transformation by plants and microbes [20]. In farmland (FL), markedly lower C/N rations in the 10-50-cm-deep soil layer likely resulted from biological immobilization of nitrogenous fertilizer.…”
Section: Indication Of Agricultural Activity C and N Sources In Agrimentioning
confidence: 99%
“…Synthetic N fertilizer can be fixed into SON through microbial immobilization and crop uptake, transformation and returning into soil as litter [20]. Therefore, the δ 15 N SON in cropland commonly decreases with the application of 15 N-depleted inorganic N fertilizers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some pathways were excavated to improve the modelling simulations such as revising the soil hydrological or N transformation modules of the existing models or constructing new models by coupling the sophisticate soil hydrological and biogeochemical processes ( e.g ., Dwivedi et al, ; Zhang et al, ). Even so, combing the existing soil hydrology‐ and biogeochemistry‐oriented models to improve the simulations might be an alternative with superiority in feasibility and time‐efficient, while this has seldom been considered in previous studies ( Zhu et al, ).…”
Section: Introductionmentioning
confidence: 99%